Neuroprotective effects of epigallocatechin-3-gallate in an experimental model of Alzheimer’s disease in rat: a histological study - Homa Rassouli (Basic and Clinical Neuroscience, 2009)
Abstract   Introduction: Neurodegeneration change is one of the hallmark symptoms of which Alzheimer’s disease (AD) can be modeled by β-amyloid injection into specific regions of brain. (-)-Epigallocatechin-3-gallate (EGCG) is a potent antioxidant agent that its role against oxidative stress and inflammation has been shown in prior studies. In the present study, we have wanted to determine whether EGCG administration protects against β-amyloid induced cell damages in rats .   Methods: Animals (male Wistar rats) divided into four groups: sham operated (SH), EGCG-pretreated sham operated (SH + EGCG), untreated lesion (L), and EGCG-pretreated lesion (L + EGCG). Animals in L, L + EGCG, and SH + EGCG groups received sterile saline or saline plus EGCG (10 mg/kg) intraperitoneally one day pre-surgery and every other day for three weeks. The lesion was induced one day after EGCG treatment by injection of water or water containing 2 nmol/µl of β-amyloid (1-40) into the hippocampal fissure. We evaluat ed the morphological changes of hippocampus specially CA3 region by nissl staining after three weeks of surgery .   Results: We found that β-amyloid (1-40) injection into hippocampus causes cell death of CA3 region in L group in comparison with SH group which also occurs in the Alzheimer’s disease. On the other hand, treatment with EGCG can improve the validity of these cells in hippocampus .   Discussion: We concluded that EGCG could be effective in protection against pathogenesis of Alzheimer’s disease .